Efektivitas Penggunaan Media Pembelajaran Interaktif Mentimeter Terhadap Peningkatan Kemampuan Berpikir Kritis Siswa - Jilan Alfarrras (Prodi Teknologi Pendidikan, 2023)
The background of this research pertains to the issue of low critical thinking abilities among students in Indonesia. The problem is associated with the lack of critical thinking skills in students' thinking methods, which is evident at SMAN 1 Cibadak where instability and inadequacy in critical thinking tend to occur during sociology lessons. This situation arises due to teachers not fully utilizing effective teaching media. The solution proposed by the researcher is the incorporation of the interactive learning media